(untitled) (Bangladesh Journal of Neuroscience, 2014)
Objective: To evaluate the effect of long term use of carbamazepine on lipid profile in adult epileptic patients Methodology: The study was conducted in the Department of Neurology at BSMMU, Dhaka over a period of 2 years from January 2010 to December 2011. Adult epileptic patients taking carbamazepine as anticonvulsant and attending the Epilepsy Clinic and Neurology OPD of BSMMU, Dhaka were the study population. A total of 107 cases and 107 controls were included in the study. Data were collected by interview of the patients, clinical examination and laboratory investigations using the research instrument Result: The mean age of case and control groups were almost identical (23.3 ± 6.8 vs. 23.8 ± 6.4 years, p = 0.972). The proportion of male and female patients was similar in both the study groups. Of the 107 cases, more than 70% had generalized epilepsy and the rest (29%) focal epilepsy. Of the 107 cases, 8% had family history of epilepsy. The prevalence of raised triglycerides and raised LDL were observed to be significantly higher in the case group than those in the control group (35.5% vs. 23.4%, p = 0.049 and 15% vs. 0.9%, p < 0.001 respectively). The prevalence of low HDL was also significantly higher in the former group than that in the latter group (43.9% vs. 18.7%, p < 0.001). The mean serum triglyceride and LDL were higher and mean HDL was lower in the case group than those in the control group. Over half (51.4%) of the case group exhibited dyslipidemia compared to the control group (27.1%). The risk of developing dyslipidemia in epileptic patients receiving carbamazepine for longer duration was nearly three-fold (95% of CI = 1.6 – 5.0) higher than that in the control group (p < 0.001). There is positive correlation between duration of carbamazepine treatment and lipid profile. Serum total cholesterol and triglycerides bear linear relationship with duration of treatment with carbamazepine (r = 0.201, p = 0.038 and r = 0.223, p = 0.021 respectively). The association of dyslipidemia with sex in epileptic patients receiving carbamazepine for more than 2 years. The proportion of dyslipdemia was considerably higher in the female patients than their male counterparts, although the difference was not statistically significant (55.3% vs. 41.9%, p < 0.211). Conclusion: A conclusion can be made from the above mentioned result that long-term use of carbamazepine in epileptic patients may cause dyslipidemia and the risk of having dyslipidemia in such patients is 3 times greater than the normal healthy population. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 27-34